Study on preparation and properties of phenol-formaldehyde-chinese fir liquefaction copolymer resin - Lin, Ruihang; Sun, Jin; Yue, Chao; Wang, Xiaobo; Tu, Dengyu; Gao, Zhenzhong (Maderas. Ciencia y Tecnología, 2025)
A new zero-waste and zero-pollution composite adhesive labeled Chinese fir-based adhesive for exterior plywood was synthesized by blending alkaline Chinese fir (Cunninghamia lanceolata) liquid with a small amount of phenol-formaldehyde (PF). The free phenol and free formaldehyde content of the Chinese fir-based adhesive were sharply decreased compared to normal PF resin by more than 50%. The synthetic adhesive show with excellent water resistance and environmental friendliness, which had a 28h boil-dry-boil wet bonding strength of 1,73MPa according to standard JIS K6806-2003 and a formaldehyde emission of 0,045mg/L according to standard JIS A1460-2003. The structural properties and their thermal properties of cured adhesives were evaluated using Fourier transform infrared (FT-IR) and differential scanning calorimetry (DSC). The FT-IR analysis confirmed the expected chemical structure as the Chinese fir liquid reacted with formaldehyde and phenol which occurred at the wavenumbers of 1733, 1698, 1652cm-1 and 1077, 1048 cm-1. Although the DSC results indicated that the Chinese fir-based adhesive’s curing need higher temperature than the control PF resin, the higher curing temperature hardly cripple the availability of Chinese fir-based resin in the plywood production.